Urban mobility with a focus on gender: The case of a middle-income Latin American city - Olivieri, Cecilia; Fageda, Xavier (Journal of Transport Geography, 2021)
This study analyzes gender differences in travel patterns for the Metropolitan Area of Montevideo, Uruguay. By applying multilevel regression models, it provides estimates of the impact of individual and contextual factors on travel behavior. The paper's findings lend support to the household responsibility hypothesis, which claims that women's travel patterns are affected by the type of household in which they live and the consequent responsibilities or roles they assume. Furthermore, gender differences in travel patterns are reinforced across census tracts. The results indicate that policy makers need to consider gender differences when seeking to enhance urban planning decisions. © 2021 Elsevier Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; déplacements urbains; environnement; géographie; géographie urbaine; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; uruguay

Gender and water insecurity in a subarctic Indigenous community - Hanrahan, Maura; Mercer, Nicholas (The Canadian Geographer / Le Géographe canadien, 2019)
Indigenous communities in Canada suffer disproportionately from compromised water insecurity, with multiple negative implications. Some attention has been paid to gender and water insecurity in developing countries, especially in sub-Saharan Africa, but the topic has been neglected for subarctic settings. We conducted long-term research in Black Tickle, a remote Inuit community in Labrador, Canada, with no piped water and limited access to potable water. Our research was aimed at understanding the multiple dimensions of water security, identifying materialist responses, and conducting a pilot project in domestic rainwater harvesting. Water security emerged as a gendered phenomenon. We supplemented our reflective analysis on this research with two focus group discussions during which Inuit women described their experiences of water security. Participants reported that their physical and mental health are undermined by water insecurity and that water is a source of multiple stresses that demand resilience. Given a developing remittance economy, gender was identified as an increasingly significant determinant of water insecurity in this subarctic community. Having to retrieve water themselves, Inuit women experience altered gender norms and a persistent values conflict in addition to physical strain. Water acquisition is an added responsibility, impacting their labour load. Alternatively, in relying on available men to retrieve water, participants reported feeling guilty and anxious and they worried about men fetching water in dangerous weather conditions and in the vicinity of dangerous wildlife. Participants’ experiences make clear the urgency for a materialist response to water insecurity in the Indigenous subarctic.
Keywords: 2000 à aujourd'hui; accès à l'eau; amériques; canada; communauté Inuit; discipline; environnement; géographie; géographie féministe; labrador; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; thématiques

Les Amériques créatives: regards croisés sur les discours et les pratiques - Pujol, Charlotte; Doré, Émilie; Drouilleau, Félicie; Villafuerte, Susana; Tinteroff Gil, Vanessa (L'Harmattan, 2017)
"Des civilisations précolombiennes à l'American Way of Life, les A mériques ont constitué un espace propice aux mythes et aux utopies. Terres de migrations, parfois forcées, elles sont constituées de multiples lieux de rencontres, de conflits, d'échanges culturels. Aujourd'hui les phénomènes d'innovation technologique, identitaire ou politique témoignent du fait que les Amériques, du Nord au Sud, demeurent un terreau de créativité. La créativité repose sur la capacité des acteurs à imaginer un autre cadre que celui dans lequel ils sont immergés. Aussi cet ouvrage s'attarde-t-il sur les discours et les pratiques individuels ou collectifs, discrets ou médiatisés, improvisés ou programmés qui participent à la fabrique des espaces et des sociétés. La diversité des regards et des situations analysées se traduit par la multi disciplinarité de ces pages. Sociologues, anthropologues, historiens, juristes, géographes, spécialistes de la littérature, du cinéma, du théâtre ou de la musique proposent des analyses ancrées dans la réalité ; leurs points de vue sont autant d'illustrations des processus créatifs. Il ne s'agissait pas là de chercher une improbable exhaustivité, mais bien plutôt de tenter de mettre en lumière la façon dont la force créative des individus et des groupes jalonne l'histoire et le devenir des nations américaines. C'est donc un kaléidoscope qui est proposé aux lecteurs, une diversité d'approches qui les font voyager de l'Alaska au Brésil."–Page 4 de la couverture
Le chapitre Nagels, Nora, 2017, « Créativité clientéliste des organisations de femmes populaires liées à l’alimentation à Lima », a été donné en lecture au cours POL4022.
Keywords: DIG; agriculture; amériques; anthropologie; arts; care; corps; cours; création; danse; discipline; environnement; géographie; musique; pol4022; premier cycle; régions géographiques; sciences humaines; sociologie; thématiques

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis